Correction to: Quality assessment with diverse studies (QuADS): an appraisal tool for methodological and reporting quality in systematic reviews of mixed- or multimethod studies - Reema Harrison; Benjamin Jones; Peter Gardner; Rebecca Lawton (BMC, 2021)
An amendment to this paper has been published and can be accessed via the original article.